Agriculture in Europe's Little Divergence: The Case of Spain - Carlos Álvarez-Nogal; Leandro Prados de la Escosura; Carlos Santiago-Caballero (European Historical Economics Society (EHES), 2015)
This paper explores the role of agriculture in Spain's contribution to the little divergence in Europe. On the basis of tithes collected by historians over the years, long-run trends in agricultural output are drawn. After a long period of relative stability, output suffered a severe contraction during 1570-1590, followed by milder deterioration to 1650. Output per head moved from a relatively high to a low path that persisted until the Peninsular War. The demand contraction, resulting from the collapse of domestic markets, monetary instability, and war in Iberia, helps to explain a less intensive use of labour and land as incentives to produce for the market sharply diminished. Agricultural output per head moved along population up to 1750. This finding confirms the view of Spain as a land abundant frontier economy. Only in the late eighteenth century a Malthusian pattern emerged.
Keywords: N53; O13; Q10; 330; agriculture; little divergence; early modern Spain; tithes; output per head